A Review of Health Infrastructure and Workforce Critical for Delivering Universal health Coverage in Uganda - Mwesigye, Francis; Odokonyero, Tonny (Economic Policy Research Centre, 2017)
Universal health coverage (UHC) - defined as the availability of quality and affordable health services for all when needed without financial hardships- can be a vehicle for improving equity in healthcare. However, access to basic healthcare is still limited, and the quality remains low in Uganda. This is mainly caused by poor health infrastructure, sub-optimal operation of health facilities, and staff absenteeism, among others. This brief summarizes the findings of a study on infrastructure and human resource gaps that impede Uganda from realizing UHC1. The study results show fundamental challenges with the health infrastructure needed to deliver UHC. Spatial inequality exists in health facility population coverage and private sector health infrastructure investments. Low health workforce density is widespread; and even if the staffing level is raised to 100% as per the set staffing norms for critical cadres, the health workforce density will still fall short of the recommended standards. The low health workforce density implies that the existing health workforce is deficient and unable to expand population-based healthcare services. Accelerating progress towards UHC requires; increased investments in health infrastructure and strengthening Public Private Partnership arrangements to establish health infrastructure in disadvantaged regions; and improvement in health workforce density by reviewing current staffing norms for critical cadres as well as increased deliberate investments in human resources for health.